2010
DOI: 10.1371/journal.pone.0011148
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals Myosin and Actin as Promising Saliva Biomarkers for Distinguishing Pre-Malignant and Malignant Oral Lesions

Abstract: BackgroundOral cancer survival rates increase significantly when it is detected and treated early. Unfortunately, clinicians now lack tests which easily and reliably distinguish pre-malignant oral lesions from those already transitioned to malignancy. A test for proteins, ones found in non-invasively-collected whole saliva and whose abundances distinguish these lesion types, would meet this critical need.Methodology/Principal FindingsTo discover such proteins, in a first-of-its-kind study we used advanced mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 32 publications
1
54
0
1
Order By: Relevance
“…Our work is part of an interdisciplinary project with the goal of finding a panel of biomarkers (proteins) in saliva that are indicative of the advance from non-cancerous lesions to cancerous ones (de Jong et al, 2010). The queries required are extremely complex.…”
Section: Graphical Relational Algebra System For Biochemistry Analysesmentioning
confidence: 99%
“…Our work is part of an interdisciplinary project with the goal of finding a panel of biomarkers (proteins) in saliva that are indicative of the advance from non-cancerous lesions to cancerous ones (de Jong et al, 2010). The queries required are extremely complex.…”
Section: Graphical Relational Algebra System For Biochemistry Analysesmentioning
confidence: 99%
“…All 15 studies were published in the 2000s, within a 10-year period (2004-2014). Fourteen papers were written in English [19][20][21][22][23][24][25][26][27][28][30][31][32][33] and one in Chinese [29].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Quantitative protein profiling is also done routinely. Quantitative studies have identified salivary proteins associated with oral cancer 11 , 12 and also systemic conditions such as 2 diabetes 13 and breast cancer 14,15 .…”
Section: Human Protein Products In Whole Salivamentioning
confidence: 99%